Adaptation of Extended Self Scale into Turkish: Validity and Relaibility Study - Katı, A. Cenk; Şevik, Ali E. (Journal of Applied And Theoretical Social Sciences, 2024)
The purpose of this study is to adapt and examine the psychometric properties of Turkish form of Extended Self Scale. The original scale was developed in the contex of “mountain biking”. This adaptation study set the contex of extended self as “aoutomobile owning”; in order to lead to other Turkish studies on self and consumption relations that might study extended self with other consumption materials. The study was conducted on 311 automobile owners over 18 years old. Scale was studied in general survey method and translation method used was translation-back translation method. The psychometric properties of the scale were examined by internal consistency, exploratory and confirmatory factor analysis and item analysis methods with SPSS and AMOS programmes. The exploratory and confirmatory factor analysis determined the scale structure with 3 factors. The model’s and CFA’s compatibility was examined through index values; and index values of the scale were determined as “acceptable” and “excellent”. The Chi-Square per Degrees of Freedom Ratio was found to be 2.758, the Comparative Fit Index (CFI) was 0.93, and the Root Mean Square Error of Approximation (RMSEA) was 0.075. The reliability of the Extended Self Scale was assessed using the internal consistency coefficient (Cronbach's Alpha) method, and the internal consistency coefficient of the scale was found to be 0.928. As the analysis of the research regarded; on self and consumption based field studies; Extended Self Scale can be defined as a scale which can be used in determining the self extension tendency.